2020
DOI: 10.1016/j.jval.2019.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lean Healthcare on Patient Flow: A Systematic Review

Abstract: Objectives: To assess the effects of lean healthcare (LH) on patient flow in ambulatory care and determine whether waiting time and length of stay (LOS) decrease after LH interventions. Methods: A systematic review was performed with close adherence to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We searched for studies of healthcare organizations applying LH interventions within ambulatory care published between 2002 and 2018. Six databases and grey literature sources were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 111 publications
4
65
0
7
Order By: Relevance
“…It encompasses the physical resources, medical care, and internal systems required to get patients from the admission to the discharge while preserving quality and patient/staff satisfaction [ 6 ]. Both inpatient and outpatient care present opportunities to increase efficiency [ 7 ]. Hence, efficiency measures and performance indicators are paramount in the survival of healthcare systems [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It encompasses the physical resources, medical care, and internal systems required to get patients from the admission to the discharge while preserving quality and patient/staff satisfaction [ 6 ]. Both inpatient and outpatient care present opportunities to increase efficiency [ 7 ]. Hence, efficiency measures and performance indicators are paramount in the survival of healthcare systems [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the NHS has historically rejected these perfectly accurate calculations and chosen instead a different path: that of focusing on 'flow' of patients. In the very simplified example above: if 100 elective patients arrive per day, then the NHS will provide staffing for only 50 beds; arranging 50 arrivals in the morning and 50 in the afternoon, with a focus on more rapid turnover [5]. More detailed modelling that has been applied to real situations of course takes into account factors like variable arrivals, different durations of treatment or bed stay, and delays to discharges [1][2][3][4][5].…”
Section: Demand-capacity Modelling In the Nhs: A Brief Historymentioning
confidence: 99%
“…Quantitatively, the amount of capacity we will need can be estimated quite accurately using the models and calculations referred to in the first paragraph. So, we already have the tools to plan ahead [1][2][3][4][5]. This will entail a fundamental shift away from the 'patient flow' focus.…”
Section: What Happens After Covid-19?mentioning
confidence: 99%
“…Despite being the focus on which to work, currently the most important indicators to measure the performance of the health care process are the length of hospital stay (LOS), i.e., the number of days comprised between the date of a patient admission and the discharge date [42], as well as the intra-hospital, 30-day, and year-round survival. Exploring Lean healthcare on patient flow, the main outcomes categorized related to the utilization of services and access to services [21,43] are the length of stay, mean waiting time to see a doctor, mean waiting time to get treatment, median time for daily treatment, median waiting time to see a professional (nurse preparation), and the median process time of being discharged. Therefore, LOS and shorter waiting times after Lean healthcare intervention were the most common measures related to process outcomes.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Lean has been implemented in different areas in healthcare as intensive care units, X-Ray, cardiology surgery, oncology, mental health units, and clinical laboratories [ 7 , 16 , 17 , 18 , 19 , 20 ]. A national survey in the United States found that 70% of hospitals used Lean healthcare or related methodologies to deal with both quality and cost issues [ 21 ]. Gonzalez-Aleu et al in 2018 analysed the critical success factors when implementing continuous improvement projects in hospitals [ 22 ].…”
Section: Introductionmentioning
confidence: 99%